The AI edge sales strategies for unleashing the power of AI to save time, sell more, and crush the competition - Blount, Jeb; Iannarino, Anthony (Ascent Audio, 2025)
Upgrade your sales process by plugging into the new power of artificial intelligence In today's cutthroat sales world, where sales professionals are constantly juggling multiple responsibilities and navigating a sea of relentless competitors, everyone is looking for an edge. What if that EDGE is found in a tool powerful enough to give you more time in your sales day, accelerate your productivity, and still leave room for the human touch that's vital to building relationships? Enter the game-changing world of Artificial Intelligence. Enter The AI Edge. The AI Edge isn't just another book about technology. Anthony Iannarino and Jeb Blount, the world's most prolific sales book authors and trainers, have come together to transform how you navigate the sales process by helping you plug into artificial intelligence. This groundbreaking, hands-on guide marries their unparalleled sales strategies, used by millions of salespeople, with the transformative power of AI. Drawing from cutting-edge research and real-world applications, the authors demystify AI and demonstrate its potential to give you more time to leverage your human advantage--creativity, empathy, and authenticity--to build deeper relationships and winning solutions that give you a leg up over the competition.
Audio book. - Online resource; title from title details screen (cloudLibrary, viewed February 21, 2025)
Keywords: Sales management -- Technological innovations; Artificial intelligence -- Financial applications; Selling -- Technological innovations; Ventes; Gestion; Innovations; Intelligence artificielle; Applications financières; Vente; Innovations; Management; Computers & Information Technology; Industries; BUSINESS & ECONOMICS; Direct; Marketing; Sales & Selling; Audiobooks; Livres audio